Efficient mRNA Delivery with mRNA Lipoplexes Prepared Using a Modified Ethanol Injection Method - Min Tang; Ayane Sagawa; Nodoka Inoue; Satomi Torii; Kana Tomita; Yoshiyuki Hattori (Pharmaceutics, 2023)
Messenger RNA (mRNA)-based therapies are a novel class of therapeutics used in vaccination and protein replacement therapies for monogenic diseases. Previously, we developed a modified ethanol injection (MEI) method for small interfering RNA (siRNA) transfection, in which cationic liposome/siRNA complexes (siRNA lipoplexes) were prepared by mixing a lipid-ethanol solution with a siRNA solution. In this study, we applied the MEI method to prepare mRNA lipoplexes and evaluated the in vitro and in vivo protein expression efficiencies. We selected six cationic lipids and three neutral helper lipids to generate 18 mRNA lipoplexes. These were composed of cationic lipids, neutral helper lipids, and polyethylene glycol-cholesteryl ether (PEG-Chol). Among them, mRNA lipoplexes containing N-hexadecyl-N,N-dimethylhexadecan-1-aminium bromide (DC-1-16) or 11-((1,3-bis(dodecanoyloxy)-2-((dodecanoyloxy)methyl) propan-2-yl) amino)-N,N,N-trimethyl-11-oxoundecan-1-aminium bromide (TC-1-12) with 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) and PEG-Chol exhibited high protein expression in cells. Furthermore, mRNA lipoplexes composed of DC-1-16, DOPE, and PEG-Chol exhibited high protein expression in the lungs and spleen of mice after systemic injection and induced high antigen-specific IgG1 levels upon immunization. These results suggest that the MEI method can potentially increase the efficiency of mRNA transfection, both in vitro and in vivo.